نشأة مصطلح الاقتصاد السياسي في العالم الإسلامي دراسة مقارنة بين الأدبيات العربية والتركية والأُردية - عبد الرزاق بلعباس (International Institute of Islamic Thought, 2017)
يتناول هذا البحث نشأة مصطلح الاقتصاد السياسي في العالم الإسلامي، ومقارنته في الأدبيات العربية والتركية والأردية، وعلاقته بالمصطلح الفرنسي économie politique، والمصطلح الإنجليزي political economy، مع تجاوز الإشارة إلى واضع المصطلح، ومسألة المناسبة في اختيار التسمية بين اللفظ المترجم والمصطلح الأصلي. فالمقصود الرئيس للبحث يتعلَّق بالعملية الإدراكية التي ولَّدت المصطلح: هل تأخذ منحى البناء على ما هو موجود أم تعلن القطيعة معه؟ وعلى هذا، يجب تسليط الضوء على مسألة تطوُّر الكتابة من منظور الحياة المعيشية الواقعية في المجتمعات المسلمة؛ ما يُحتِّم الانتقال من دراسة تاريخ الفكر الاقتصادي الإسلامي إلى دراسة تاريخ الفكر الاقتصادي في هذه المجتمعات. This study deals with the origin of the concept of 'political economy' in the Muslim world through a comparison between Arabic, Turkish and Urdu literature. The study found that the concept entered the Muslim world through the translation of the French term 'économie politique' and the English term 'political economy'. The study recommends going beyond the concern of who introduced first the concept, and the suitability of the translated or original terms. The central issue is the cognitive process that has generated the concept; whether adopting a constructive approach to what exists or to break with it. The study recommends shedding light on the evolution of writings on the economic life in Muslim societies and calls for a transition from the study of the history of economic thought in Islam to the history of economic thought in Muslim societies.